Meat protein based bioactive peptides and their potential functional activity: a review. (27th February 2019) - Xing, Lujuan; Liu, Rui; Cao, Songmin; Zhang, Wangang; Guanghong, Zhou
Summary: Bioactive peptides are the general name for the short amino acid sequences, which could be generated from the hydrolysis of parent proteins including beef, pork, mutton, chicken, duck and various species of marine organisms. Drying, curing, ripening and fermentation are particular procedures for meat flavour and also important for the releasing of bioactive peptides from parent proteins. Once being released, the peptides would play bioactive roles beyond their nutritional values. The physiological activities of meat‐derived peptides have been demonstrated to have antioxidative, antihypertensive, antimicrobial, opioid, antithrombotic and other bioactive effects. The regulation on immunological, gastrointestinal and neurological responses of those bioactive peptides supplies a vital base for the prevention of hypertension, obesity, diabetes and other metabolic disorders. In this review, we summarised the current studies on meat derived bioactive peptides along with their physiological functions to supply the overall understanding of the health benefit of bioactive peptides. Abstract : Bioacive peptides in meat were mainly generated in the proteins from chickens, cows, pigs, sheep and horses, where the release of bioactive peptides would also rely on the hydrolytic process by the action of exogenous and endogenous enzymes, which include the pepsin, trypsin, papain, cathepsin, aminopeptidase etc. Once been released from the parent protein, the peptide sequences would play functional actions, like anti‐hypertension, anti‐oxidant, anti‐microbial and others.